Educação não escolar e o espaço de atuação do pedagogo na socioeducação do Amazonas - Costa, Nayara de Souza (Brasil, 2022)
The present Course Conclusion Work (TCC) investigates the non-schooling education and the Pedagogue's performance space in the socio-educational institutions, as well as the selection process of this professional in the State of Amazonas. To this end, we discuss and present conceptions about the Science of Education, non-school education, Social Pedagogy, and Social Education. The research in question is in line with scientific initiation projects, has an exploratory character and uses the documental and bibliographic method based on the precepts of qualitative research. Its general objective is to make considerations about the school and non-school social function of the Pedagogue and its context of insertion in the social-educational system of Manaus, and the specific objectives are: a) to identify the theoretical contributions of Social Education and the space of non-school performance in the social-educational system; b) to verify the organization of the social-educational system of Amazonas and the relationship with school education; and, c) to point out how the profile of the Pedagogue is structured in the Simplified Selection Process of the social-educational system of Amazonas.